2004
DOI: 10.1038/sj.bjc.6601562
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with two different models of cancer genetic services in south-east Scotland

Abstract: There is a need to integrate primary-and secondary-care cancer genetic services, but the most appropriate model of service delivery remains unclear. This study reports patients' expectations of breast cancer genetic services and a comparison of their satisfaction with two service models. In the first model, risk assessment was carried out using mailed family history data. Women estimated as being at high/moderate risk were offered an appointment at the familial breast cancer clinic, and those at low risk were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 20 publications
3
40
0
2
Order By: Relevance
“…Similar levels of patient satisfaction have been reported in other trials of genetic counselling services for risk of breast cancer (Brain et al, 2000;Hopwood et al, 2004;Holloway et al, 2004). In addition, the acceptability of the genetic nurses counsellors was high among referring GPs in both trial settings.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar levels of patient satisfaction have been reported in other trials of genetic counselling services for risk of breast cancer (Brain et al, 2000;Hopwood et al, 2004;Holloway et al, 2004). In addition, the acceptability of the genetic nurses counsellors was high among referring GPs in both trial settings.…”
Section: Discussionsupporting
confidence: 77%
“…In the trial by Brain et al (2000), the addition of specialist genetic assessment to the standard surgical consultation had no effect on patients' psychological outcomes, risk perception or satisfaction, although knowledge of cancer genetics showed greater improvement. The other RCT found community-based genetic nurse specialists to be generally comparable to the standard service (consultant geneticist), in terms of psychosocial outcomes and patient satisfaction, with the additional benefit of lower staff and patient costs (Fry et al, 2003;Holloway et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The models of care in operation at the WMRGU broadly reflect genetics service provision in the UK. Similar to most UK genetics units, the WMRGU has set up a triage system as a means of regulating access to cancer genetics services, see for examples of triage systems in other NHS regions (Holloway et al 2004;Elwyn et al 2002;Wilson et al 2005). Counselees fill in a family history form.…”
Section: Introductionmentioning
confidence: 99%
“…Process issues, such as satisfaction with consultation waiting time, location, duration of counselling sessions, and type of service provider, have been examined in a number of studies (Shiloh et al, 1990;Bernhardt et al, 2000;Brain et al, 2000;Metcalfe et al, 2000;Wilson et al, 2000;Holloway et al, 2004;Pieterse et al, 2005a, b). Client outcomes are more difficult to measure than process issues, but are more salient for evaluating and informing service delivery (Clarke et al, 1996;Cappelli et al, 2001).…”
mentioning
confidence: 99%
“…Studies of expectations before genetic counselling have shown that clients often do not know the procedure or structure of the counselling appointment, sometimes resulting in the client feeling that he or she was inadequately prepared (Hallowell et al, 1997;Stadler et al, 1998;Berkenstadt et al, 1999;Bernhardt et al, 2000;Holloway et al 2004). Studies of preferences measured before genetic counselling have further shown that clients have high preference for information, although it is difficult to interpret findings regarding preferences for aspects other than information given clients' lack of knowledge about the counselling process before attendance (Cohn et al, 2003;Tiller et al, 2005).…”
mentioning
confidence: 99%